Force fields for macromolecular assemblies containing Diketopyrrolopyrrole and Thiophene - Jiang, Ling; Rogers, David M.; Hirst, Jonathan D.; Do, Hainam (NLM (Medline), 2020)
Utilizing a force-matching procedure, we parametrize new force fields systematically for large conjugated systems. We model both conjugated polymers and molecular crystals that contain diketopyrrolopyrrole, thiophene, and thieno[3,2-b]thiophene units. These systems have recently been found to have low band gaps, which exhibit high efficiency for photovoltaic devices. The equilibrium structures, forces, and energies of the building block chromophores, diketopyrrolopyrrole, thiophene, and thieno[3,2-b]thiophene computed using our parameters are comparable to those computed using the reference electronic structure method. We assess the suitability of this new force field for electronic property calculations by comparing the electronic excitation properties computed along classical and ab initio molecular dynamics trajectories. For both trajectories, we find similar distributions of TDDFT-calculated excitation energies and oscillator strengths for the building block chromophore diketopyrrolopyrrole-thieno[3,2-b]thiophene. The structural, dynamic, and electronic properties of the macromolecular assemblies built upon these chromophores are characterized. For both polymers and molecular crystals, pronounced peaks around 0° or 180° are observed for the torsions between chromophores under ambient conditions. The high planarity in these systems can promote local ordering and π–π stacking, thereby potentially facilitating charge transport across these materials. For the model conducting polymers, we found that the fluctuations in the density of states per chain per monomer is negligibly small and does not vary significantly with chains comprising 20–40 monomers. Analysis of the electron–hole distributions and the transition density matrices indicates that the delocalized length is approximately 4–6 monomers, which is in good agreement with other theoretical and experimental studies of different conducting polymers. For the molecular crystals, our investigation of the characteristic time scale of the fluctuation in the excitonic couplings shows that a low-frequency vibration below 100 cm–1 is observed for the nearest neighbors. These observations are in line with previous studies on other molecular crystals, in which low-frequency vibrations are believed to be responsible for the large modulation of the excitonic coupling. Thus, our approach and the new force fields provide a direct route for studying the structure–property relations and the molecular level origins of the high efficiency of these classes of materials.